An Evaluation of the Assistance Offered by Guarantee and Loan Funds to SMEs - Sułkowski, Rafał (Journal of Public Governance, 2009)
The article is an introduction to an effectiveness analysis of microloan funds and guarantee funds operating in Poland as well as their assistance to SMEs. It describes the role of SMEs in the economy and the major barriers of their development, eg. their limited access to capital. The article describes functions and features of microloan funds and guarantee funds which aim to create an effective financial system for SMEs.